Effect of synthetic feed additives on growth and leucocyte count in koi carp, Cyprinus carpio var. koi Linnaeus - James, R; Sampath, K; Mary, T Roseline Sheeba (Indian Journal of Fisheries, 2011)
Effect of different levels (0,1,3,6 and 9%) of synthetic feed additives, nutriwin and frankmin on growth and leucocytes count were studied in the ornamental koi carp, Cyprinus carpio var. koi for a period of 100 days. The experimental diets were prepared with 40% protein. The mean body weight of koi carp increased with progression of time, however, the rates of feeding, conversion and conversion efficiency gradually decreased with progression of time. The dietary administration of 6% nutriwin and 3% frankmin elicited the maximum feeding and growth rates, while 9% nutriwin and 6-9% frankmin reduced the feeding and growth rates. It suggests that lower doses (3% frankmin and 6% nutriwin) have anabolic effect stimulating feed intake and growth and catabolic effect at higher doses causing reduction of growth. Similar trend was obtained in feed conversion ratio also. Fish fed with 3% frankmin and 6% nutriwin showed highest number of leucocytes, neutrophils, monocytes and lymphocytes, therefore these are considered as optimum doses. Among the two feed additives, frankmin appears to be more economical for aquaculture production than nutriwin as it is required in less concentration.